Prima facie - García Yzaguirre, Víctor (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The objective of this article is to identify and briefly characterize the ways in which jurists understand the prima facie character of a norm. For this, I will reconstruct the two meanings that the specialized literature usually attributes to it: i) as a way of presenting a problem of lack of information about the scope of a norm (prima facie in an epistemic sense); and ii) as a way of presenting a problem of indeterminacy generated because of the lack of hierarchy between norms (prima facie in the normative sense).
Keywords: cancelability; superability; exceptions; norms; duties